Integrating Mediation in the Corporate Culture as a Sustainable Practice - Alexandrova, Nedyalka (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This article examines the integration of mediation into corporate culture as a sustainable practice, emphasizing its capacity to transform conflict into a strategic asset that enhances organizational resilience, employee well-being, and long-term corporate sustainability. Drawing upon an extensive review of the literature from conflict resolution and sustainability studies, the article elucidates the mechanisms by which mediation contributes to a healthier work environment and fosters ethical and adaptive management practices. Mediation possesses all the essential characteristics of a sustainable practice, and its integration into corporate culture could contribute to enhancing business sustainability. Among these characteristics are cost reduction, increased stakeholder satisfaction, the achievement of lasting solutions, and the resolution of conflict situations.